Comparison of Microbial Populations in the Blood of Patients With Myocardial Infarction and Healthy Individuals - Khan, Ikram; Khan, Imran; Kakakhel, Mian Adnan; Xiaowei, Zhang; Ting, Mao; Ali, Ikram; Fei, Yu; Jianye, Zhou; Zhiqiang, Li; Lizhe, An (Frontiers in Microbiology, 2022)
Increased bacterial translocation in the gut and bloodstream infection are both major comorbidities of heart failure and myocardial infarction (MI). However, the alterations in the microbiome in the blood of MI patients remain unclear. To test this hypothesis, we conducted this case-control study to explore the microbiota compositions in the blood of Chinese MI patients. Using high-throughput Illumina HiSeq sequencing targeting the V3-V4 region of the 16S ribosomal RNA (rRNA) gene, the microbiota communities in the blood of 29 MI patients and 29 healthy controls were examined. In addition, the relationship between blood microbiome and MI clinical features was investigated. This study revealed a significant reduction in alpha diversity (Shannon index) in the MI group compared with healthy controls. Also, a significant difference was detected in the structure and richness between MI patients and healthy control. Actinobacteria phylum, Actinobacteria class, Bifdobacteriales order, Bifidobacteriaceae family, and Bifidobacterium genus were significantly abundant in the MI group, while Bacteroidetes phylum, Bacteroidia class, and Bacteroidales order were significantly enriched in healthy controls p<0.05. Moreover, the functional analysis revealed a significant variation between both groups. For instance, enrichment of genes decreased in three amino acid metabolism pathways: nucleotide transport and metabolism, coenzyme transport and metabolism, and lipid transport and metabolism, among others. Our study will contribute to a better knowledge of the blood microbiota, which will lead to improved MI diagnosis and therapy. Further study is needed to determine the role of the blood microbiota in human health and disease.